Management of cardiorespiratory arrest for High School and pre-university students in the city of Rio Verde, State of Goiás, Goiás, Brazil (Research, Society and Development, 2024)
Objective: The objective of this article is to present a study on the recognition of cardiorespiratory arrest (CPA) and the performance of cardiopulmonary resuscitation (CPR) covering the lay population (those who are not health professionals. Knowing this, it would be possible that the implementation of classes on CRA management in an extra-hospital environment in schools and pre-university entrance exams could make the lay population more prepared to deal with this situation. Methodology: It is a field action research with participant observation of the researchers, where there was a primary involvement with the propagators of knowledge about PCR with the target audience. Results and discussion: Studies indicate that the main public that attends these CPAs – cardiorespiratory arrests are laypeople, especially adolescents and children, and often, due to lack of knowledge about it, do not call for help in time. Anyone, even if they are not a health professional, can perform them, as long as they are trained to provide the the initial care, stabilizing the victim, maintaining vital functions and thus avoiding the worsening of his condition until the arrival of specialized medical assistance. Final Considerations: The simple fact of being able to identify a PCR, call 192 and ask for the AED is already being a great advance for the community. Considering that in our country the culture of teaching first aid from the base of teaching children has not yet been added, we still have a lot to evolve.